Islamic Religious Education In Police Institutions: The Dialectic Between Moral Doctrine and The Reality of Officer Behavior - Edo Ferdian; Daud Ridwan; Muhammad Adz Dzahabie; Annisa Maryam Nurrohmah; Khoiriyah (Education Reserach Center, 2026)
This research aims to analyze the position of Islamic Religious Education in the police institution as a normative moral doctrine, examine the gap between ideal values ​​and the actual behavior of officers, and identify structural, cultural, and pedagogical factors that influence the effectiveness of the internalization of PAI values ​​in the formation of police professional ethics. This study uses a qualitative approach with a descriptive-analytical research type. The analytical framework used is a normative-empirical approach through the perspectives of das sollen and das sein. The research data are sourced from internal police policy documents and regulations, scientific literature in the form of books and articles from accredited national journals, and relevant previous research. Data collection techniques are carried out through documentation studies and literature studies, which at certain stages can be supplemented with limited interviews as supporting data. Data analysis is carried out qualitatively through the process of data reduction, data presentation, and drawing thematic and critical conclusions. The results of this study indicate that Islamic Religious Education in the police force formally holds strong legitimacy as the ethical foundation for police development. However, the internalization of Islamic Religious Education values ​​in the professional behavior of officers has not been optimal. As a result, Islamic Religious Education tends to function as a symbolic moral doctrine that has not been fully integrated with the realities of police duties and ethical dilemmas.